An Economic Approach to Family Institution: Regulation of Spouses’ Property Relations in the Republic of Lithuania - Perkumienė, Dalia; Čiulevičienė, Vida (Ekonomika, 2006)
The paper analyses the problem which is relevant both theoretically and practically, since it tries to disclose family as an economic institution credited with important financial advantages, and it provides different economic and social benefits such as tax exemptions, inheritance, child and spouse maintenance, social security and immsigration. This position is revealed analysing the regulation of legal property relations between spouses by laws, various scientific and legal literary works related to this topic as well as court practice.At the moment of marriage commencement, property relations used to acquire a significant value in a major part of traditional societies: in some countries, bride’s parents would award their daughters with dowry, the size of which very often determined the groom’s choice; in other countries, especially in the East, a groom would pay a ransom for his bride. In some countries such customs are extant to the present day and constitute a traditional part of a marriage settlement. In different cultures the bride’s parents must give away part of their property to the newlyweds (known as a dowry). The dowrygiving practice is similar in such countries as Greece, Egypt, India, and China. The type of property called wife’s property exists in the countries of different religions and customs. For instance, the Hindu law entitles the wife’s property as Stridhanam.